Effect of extraction procedures on the chemical structure, antitumor and anticoagulant properties of ulvan from Ulva lactuca of Tunisia coast. (1st February 2021) - Guidara, Mariem; Yaich, Hela; Amor, Ikram Ben; Fakhfakh, Jawhar; Gargouri, Jalel; Lassoued, Saloua; Blecker, Christophe; Richel, Aurore; Attia, Hamadi; Garna, Haikel
Graphical abstract: Highlights: Ulvans from green algae Ulva lactuca were extracted by various extraction procedures. Peculiar structures of ulvan extracts were determined by Fourier Transform Infrared and Nuclear Magnetic Resonance methods. Enzymatic-chemical extract has the greatest cytotoxic activity against HeLa cancer cell lines. Acid extracts promoted the inhibition of cancer cells and the growth of normal cells. Acid extracts revealed the highest anticoagulant activity, in Activated Partial Thromboplastin Time and Thrombin Time assays. Abstract: The effect of extraction procedures on chemical composition, structural, antitumor and anticoagulant properties of the sulphated polysaccharide 'ulvan' from the green seaweed Ulva lactuca were investigated. The structural features of ulvans were carried out by FTIR and by one- and two- dimensional 1 H and 13 C NMR spectroscopic. The ulvans were mainly composed of rhamnose, xylose, and uronic acid. Chemical and spectroscopic analyses demonstrated that ulvans were constituted of (1→4)-β-glucuronic acid, (1→3, 4)-α-L-rhamnose-3-sulphate and (1→4)-α-xylose. The extraction procedures effect were observed in chemical structure, Mw and biological activities. Cytotoxic activity of enzymatic-chemical extract on cervical cancer cells (HeLa) (IC50 = 1000 μg/mL) was higher than on normal peripheral blood lymphocytes cells (PBL). Acid extracts promoted to reduce HeLa cells and to grow PBL cells. At high concentrations, acid extracts showed the highest APTT and TT clotting time. Antitumoral and anticoagulant activities of ulvans from Ulva lactuca promote their use as effective therapeutic agent.